Safety, Tolerability, and Effects of a Single Subcutaneous Administration of SP16 – a SERPIN-like, Small Peptide Agonist of the Low-Density Lipoprotein–like Receptor 1– on the Acute Inflammatory Response in Patients With ST-Segment Elevation Myocardial Infarction. Issue 5 (November 2022) - Van Tassell, Benjamin W.; Wohlford, George F.; Del Buono, Marco Giuseppe; Damonte, Juan Ignacio; Markley, Roshanak; Turlington, Jeremy; Kadariya, Dinesh; Talasaz, Azita; Ho, Jane; Marawan, Amr; Thomas, Georgia K.; Austin, Dana; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Modulation of the inflammatory response is a promising therapeutic strategy in acute myocardial infarction. The novel approach is based on the anti-inflammatory and cytoprotective properties mediated by the engagement of the low-density lipoprotein‒related protein 1 (LRP1) receptor. SERPIN peptide 16 (SP16) is a synthetic, selective LRP1 agonist. We herein present the results of a study with a single subcutaneous administration of SP16 in 10 patients with STEMI, to appraise its safety and tolerability and explore the effects on the acute inflammatory response, infarct size, and cardiac function. Methods: Ten patients with ST-segment elevation myocardial infarction (STEMI) were enrolled within 12 hours of symptoms onset and 6 hours of percutaneous coronary intervention in a single-center, single-arm, open-label study of a single subcutaneous administration of SP16 (0.2 mg/kg). Serial clinical biomarkers and echocardiography data were collected up to 12 months. The data are presented separately for the treatment group and compared with historical controls from a placebo-treated arm in a recently completed clinical trial (N = 28) with similar enrollment criteria. Results: All ten patients with STEMI received subcutaneous administration of SP16, 381 [272–478] minutes after percutaneous coronary intervention, without any treatment-related adverse events. The area under the curve for C-reactive protein was 133 [46–528] mg·d/L in the SP16-treated group versus 286 [141–581] mg·d/L in the historical placebo-treated group ( P = 0.161). The area under the curve for creatine kinase–myocardial band was 1432 [675–3089] ng·d/mL in the SP16-treated group versus 2367 [830–4750] ng·d/mL in the historical placebo-treated patients ( P = 0.428). Left ventricular ejection fraction was 46% [39–54] at baseline and 51% [46–58] at 1 year follow-up in SP16-treated patients (interval change 5% [−0.3% to +9%] P = 0.05) and 44% [38%–56%] at baseline and 53% [43%–59%] at 1 year follow-up in historical placebo-treated patients (interval change 3% [−5% to 10%], P = 0.305). Conclusion: A single subcutaneous administration of SP16, a synthetic targeted LRP1 agonist, was safe and well-tolerated in patients with STEMI. A trend toward reduction in the inflammatory response and infarct size with SP16 was noted; however, the sample size for this study was not based on formal statistical criteria. More extensive studies are planned to determine the clinical efficacy of SP16 in STEMI. NCT: NCT04225533.